Science interest of grade II children in Tuguegarao district no. 2 - Gayagoy, Cipriana Singson 1925- (s.n.], 1970)
The aim of the study is to describe and compare the science interests of Grade II children. The identification of children's science interest is based on the belief that a sound science curriculum should have this as one of its bases. The results of the study provide science educators with better insight into the possible solutions to problems that beset teachers in the teaching of science. It also serves as a guide to those who are involved in the development of the science curriculum for Grade II and in the preparation of textbooks and other curriculum materials.